Effect of Resistance Training and Fish Protein Intake on Motor Unit Firing Pattern and Motor Function of Elderly - Watanabe, Kohei; Holobar, Aleš; Mita, Yukiko; Kouzaki, Motoki; Ogawa, Madoka; Akima, Hiroshi; Moritani, Toshio (Frontiers in Physiology, 2018)
We investigated the effect of resistance training and fish protein intake on the motor unit firing pattern and motor function in elderly. Fifty healthy elderly males and females (69.2 ± 4.7 years) underwent 6 weeks of intervention. We applied the leg-press exercise as resistance training and fish protein including Alaska pollack protein (APP) as nutritional supplementation. Subjects were divided into four groups: fish protein intake without resistance training (APP-CN, n=13), placebo intake without resistance training (PLA-CN, n=12), fish protein intake with resistance training (APP-RT, n=12), and placebo intake with resistance training (PLA-RT, n=13). Motor unit firing rates were calculated from multi-channel surface electromyography by the Convolution Kernel. A greater improvement in the motor function, i.e., chair-stand test, was observed in APP-RT compared with PLA-RT at 6W (p < 0.05). Changes in the motor unit firing pattern were mainly noted within motor units with a low-recruitment threshold in APP-RT and PLA-RT at 3 and 6W (p < 0.05), but not in APP-CN or PLA-CN (p > 0.05). Time courses of changes in the results of the chair-stand test and motor unit firing rate were different between APP-RT and PLA-RT. These findings suggest that, in the elderly, the effect of resistance training on the motor unit firing rate is observed in motor units with a low-recruitment threshold, and additional fish protein intake modifies these changes in motor unit firing patterns and the motor function following resistance training.